The effects of size and surface-coating of CuO-nanoparticles on extractable Cu and enzyme activities in soil - Kaushik Adhikari; Anil Timilsina; Hao Chen (Elsevier, 2024)
The application of nano-enabled agricultural chemicals introduces metal oxide nanoparticles (NPs) into agricultural soils, with CuO-NPs as one of the most common. Because CuO-NPs can dissolve to release Cu ions, they often display different environmental impacts. As such, it is essential to comprehensively examine the Cu bioavailability of CuO-NPs in soil and its impacts on soil enzyme activities, which are critical for soil health. This research examined how variations in CuO-NP size (10, 40, and 80 ​nm), surface coatings (polyvinylpyrrolidone and polyacrylic acid), and concentrations (100, 250, and 500 ​mg/kg) influenced the extractable Cu in soil and their impacts on selected soil enzymes (acid phosphatase and dehydrogenase). Main indicators were quantified after a 30-day incubation period. The bioactive Cu related to CuO-NPs as determined via CaCl2 and DTPA extractions indicated that 10 ​nm CuO-NPs had the highest extractable Cu across all incubation times. Besides, polyvinylpyrrolidone and polyacrylic acid coating had little impact on extractable Cu compared to uncoated ones. Unlike CuSO₄, extractable Cu concentrations in CuO-NPs spiked soil increased over time. CuO-NPs dissolution was negatively correlated with soil pH. CuO-NPs after 24 ​h short-term exposure significantly inhibited both enzyme activities across all tested concentrations, with smaller NPs showing greater effect. However, reduced toxicity to enzyme activities was observed after 30 days. A strong negative correlation was observed between CuO dissolution and enzyme activities after 1 and 30 days, indicating Cu ions are the main toxicity source. This study elucidates that CuO-NP size, concentration, surface coating, and exposure duration collectively impact the interactions of CuO-NPs with soil enzymes, providing critical insights into the sustainable use of nanotechnology in agriculture.